Sleep Disturbances and Sleep Disordered Breathing Impair Cognitive Performance in Parkinson’s Disease - Hermann, Wiebke; Schmitz-Peiffer, Henning; Kasper, Elisabeth; Fauser, Mareike; Franke, Christiana; Wienecke, Miriam; Otto, Karolin; Löhle, Matthias; Brandt, Moritz D.; Reichmann, Heinz; Storch, Alexander (Frontiers in Neuroscience, 2020)
Background: Sleep disturbances and impairment of cognitive performance are among the most frequent non motor symptoms in Parkinson’s disease with negative implications on quality of life of patients and caregivers. Despite the fact, that sleep disturbances are a major issue in PD patients, only limited data are available regarding interactions of sleep disturbances and cognitive performance. Objective: This post-hoc analysis of the RaSPar trial was therefore designed to further elucidate sleep disturbances and their impact on cognition in PD. Methods: Twenty-six PD patients with sleep disturbances were evaluated thoroughly including assessments of patients subjective and objective sleep quality by interview, questionnaires and polysomnography (PSG). Cognitive performance was assessed by Parkinson’s Neuropsychometric dementia assessment and Test of Attentional Performance (PANDA, TAP) and associations of sleep and cognitive function were evaluated. Results: We did not detect differences in cognitive performance between patients with and without RBD. Instead cognitive impairment, particularly affecting cognitive domains attention, executive function/working memory and semantic memory, was associated with impaired PSG measured sleep quality (e.g., sleep efficiency) and sleep disordered breathing (Apnea-Hypopnea-Index >5/h). Sleep efficiency was negatively associated with divided attention (r=-0.640, P=0.018; Pearson correlation test). Global cognitive performance was decreased in patients with sleep disordered breathing (PANDA score 23.2±3.5 vs. 26.9±2.2, P=0.020, unpaired two-sided t-test). Conclusion: Sleep apnea and other sleep disturbances impair cognitive performance in PD and should be evaluated in routine care and treatment options such as continuous airway pressure therapy should be considered. The influences of sleep disturbances and their treatment options on cognitive performance should be further evaluated in future multicenter trials.